Righting the balance : how you can help protect America - Serwer, Daniel Paul, 1945- (Potomac Books, an imprint of the University of Nebraska Press, 2013)
When Daniel Serwer is asked what he does, he often replies, "I make peace. I put it in cans and ship it abroad." That pursuit of peace took him to Iraq, Afghanistan, Libya, Egypt, and many places in between during Serwer's forty years in public service. His experiences at the sharp end of foreign policy have shaped his view of the United States' ability to protect itself from today's threats. In Righting the Balance, Serwer focuses on what should be done to protect the United States by offering alternatives that move away from an exclusive reliance on the military. Most fundamentally, Serwer stresses that civilians—diplomats, aid workers, UN officials, humanitarians, police trainers, lawyers, judges, entrepreneurs—can and should be involved in helping bring about peace. Righting the Balance offers a proposal to reform our civilian institutions for the twenty-first century so that they can help deliver real results in the search for peace even when confronting difficult conditions in faraway places. -- Provided by publisher.